Seizures Induces Hypoxia and Hypoxia Induces Seizures: A Perverse Relationship that Increases the Risk of SUDEP - Auzmendi, Jerónimo Andrés (2020)
He uttered a cry and was seen to be rubbing his hands together. His pulse wasimmediately examined for but was not palpable.Hypoxia is a biological stimulus capable of promoting both rescue and survivalmechanisms, as well as triggering a sequence of irreversible events that lead to deathof cell, tissue and even individual. Brain and heart functions depend critically onadequate energy supply and they are highly susceptible to hypoxic conditions.Adequate oxygen supply is needed for the brain and heart to metabolize glucose asits major energy source. But how many type of hypoxia we know, and how muchsevere is the hypoxic condition, when more than one type of hypoxia aresimultaneously acting. Four types of hypoxia are distinguished in medicine: α- thehypoxemic hypoxia, due to a decrease in the amount of breathable oxygen orcardiopulmonary failure, b- the anemic hypoxia related with decreased amount offunctional hemoglobin, c- the stagnant hypoxia, secondary to reduced or unevenlydistributed flow of blood distribution to the tissues, and mainly result from heartdisease that impairs the circulation; and d- the histotoxic hypoxia, in which the tissuecells are poisoned and are therefore unable to make proper use of oxygen.